2012
DOI: 10.1007/s10035-012-0312-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a massive intruder in a homogeneously driven granular fluid

Abstract: A massive intruder in a homogeneously driven granular fluid, in dilute configurations, performs a memory-less Brownian motion with drag and temperature simply related to the average density and temperature of the fluid. At volume fraction ∼10-50% the intruder's velocity correlates with the local fluid velocity field: such situation is approximately described by a system of coupled linear Langevin equations equivalent to a generalized Brownian motion with memory. Here one may verify the breakdown of the Fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The validity of an equilibrium-like Fluctuation-Dissipation relation was observed, with an effective temperature which -as orders of magnitude -was "related to the granular temperature", a fact which is reminiscent of the observations discussed in the previous paragraphs, but cannot be fully evaluated since the real granular temperature was not measured. Most recent studies, both theoretical [234,236,116,113,247] and experimental [237], have shown that when the granular is a liquid and not a gas, deviations from the equilibrium Fluctuation-Dissipation relation are observed: most importantly, such deviations are not well described by an effective temperature. In granular liquids, as a matter of fact, granular temperature is much less useful than in gases, and cannot be replaced by some other temperature for the purpose of an effective description.…”
Section: Granular Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The validity of an equilibrium-like Fluctuation-Dissipation relation was observed, with an effective temperature which -as orders of magnitude -was "related to the granular temperature", a fact which is reminiscent of the observations discussed in the previous paragraphs, but cannot be fully evaluated since the real granular temperature was not measured. Most recent studies, both theoretical [234,236,116,113,247] and experimental [237], have shown that when the granular is a liquid and not a gas, deviations from the equilibrium Fluctuation-Dissipation relation are observed: most importantly, such deviations are not well described by an effective temperature. In granular liquids, as a matter of fact, granular temperature is much less useful than in gases, and cannot be replaced by some other temperature for the purpose of an effective description.…”
Section: Granular Liquidsmentioning
confidence: 99%
“…A simple example is provided, again, by the case of a massive intruder M m [113,247]. For the purpose of describing the velocity autocorrelation of the tracer and its linear response, the model in Eqs.…”
Section: Granular Liquidsmentioning
confidence: 99%
“…where F ν (v, t|v 0 ) is the conditional velocity distribution of the tracer at time t knowing it had velocity v 0 at time 0, i.e. it is the time-dependent distribution F ν (v, t) with the initial condition F ν (v, 0) = δ(v − v 0 ), which may also be represented using the implicit formulation (15). We may thus define the auxiliary function…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of ulterior developments on this modified Lorentz problem focused on asymptotic and relaxation properties [8][9][10][11][12][13]. Recently, the model was used as a paradigm for the study of microscopic entropy production and fluctuation relations in non equilibrium systems [14,15], and to discuss the force-velocity relation [16] as measured in experiments [17].…”
Section: Introductionmentioning
confidence: 99%
“…There also exist a few simulation studies of F d acting on an intruder in a d = 2 granular medium [40][41][42][43]. Bharadwaj et al [42] obtained F d for an immersed cylinder in a stream of solid particles.…”
Section: Introductionmentioning
confidence: 99%